RARE-02. POLYAMINE PATHWAY INHIBITION IS A POTENT NOVEL THERAPEUTIC STRATEGY AGAINST DIFFUSE INTRINSIC PONTINE GLIOMA. (1st June 2021) - Khan, Aaminah; Gamble, Laura; Upton, Dannielle; Yu, Denise; Pandher, Ruby; Mayoh, Chelsea; Burns, Mark R; Norris, Murray D; Haber, Michelle; Tsoli, Maria; Ziegler, David S
Abstract: Diffuse intrinsic pontine glioma (DIPG) is an aggressive paediatric brainstem tumour, with a median survival of less than 1 year. Polyamines are intracellular polycations that control important aspects of cell growth and are often upregulated in cancer. Difluoromethylornithine (DFMO) is an FDA-approved inhibitor of the enzyme ornithine decarboxylase (ODC1) which is a key driver of polyamine synthesis. We investigated the efficacy of polyamine pathway inhibitors as a therapeutic strategy against DIPG. We found that there were high over-expression levels of polyamine synthetic enzymes from DIPG primary patient samples and neurosphere cultures. Using alamar blue cytotoxicity and soft-agar clonogenic assays, we found that DFMO inhibited the proliferation of DIPG neurospheres. However, DIPG cells compensated for DFMO inhibition by increasing expression of the polyamine transporter SLC3A2 and subsequently uptake of polyamines. Addition of polyamine transporter inhibitor AMXT 1501 to DFMO led to synergistic inhibition of DIPG proliferation in vitro . Consistent with the in vitro results, the combination of DFMO and AMXT 1501 significantly prolonged the survival of mice bearing 3 different DIPG orthografts with at least 2/3 of the animals surviving up to 160 days. Addition of irradiation further improved the survival of mice treated with DFMO and AMXT 1501. Differential expression analysis showed that the polyamine transporter, SLC3A2, was significantly overexpressed in DIPG and other paediatric brain tumours including high grade gliomas compared with normal brain tissue. Our results suggest that DIPG tumours are exquisitely sensitive to polyamine inhibitors, and that dual blockade of polyamine synthesis and transport is a promising novel therapeutic strategy. AMXT 1501 is currently in clinical development, and following completion of an adult Phase 1 trial, a clinical trial of AMXT 1501 + DFMO for DIPG patients is planned through the CONNECT consortium.